Pattern of Limb Injuries in Road Traffic Accident: A Cross-Sectional Study in a Tertiary Health Care Centre in North East India - Devi , S E; Phanjoubam , M; Angami , A; Devi, T M (Journal of Indian Academy of Forensic Medicine, 2023)
According to World Health Organization, road traffic accident claims 1.2 million deaths annually and causes up to 50 million non-fatal  injuries. Alimb injury is any injury to a limb, either a leg or arm, or to the toes and fingers. Limb injuries include broken bones (cracked or  fractured bones, eg. a broken arm), dislocations (when a bone has been moved or dislodged, eg. a dislocated shoulder), sprains (injuries to  ligaments, eg. a sprained ankle), strains (injuries to muscles, eg. a strained thigh), nail injuries (injuries to toenails and fingernails, eg., a  stubbed toe), and bruises (colored marks caused by bleeding under the skin due to an impact). Across-sectional study was conducted in the  mortuary of a tertiary health care centre in North-East India. The study was done from September 2019 to August 2021. All road traffic  accident cases which were brought for medico legal autopsy were included. From the present study, it was found that maximum number of  victims was due to two-wheeler accidents and most of the fatalities occurred after reaching hospital, mostly due to lack of prompt aid for  the victim and less trauma center in the region. Injuries mostly seen are abrasion and a few cases of fracture. The cause of death is injury to  major vessels involved in the fracture causing shock and hemorrhage. It is also observed that multiple limb injuries and limb injuries  associated with fracture could be fatal which is significant (p< .001).
Keywords: Road traffic accident; Limb injuries; Two wheeler accident; Abrasion; Fracture; Fatality